A Novel Circular RNA circITSN2 Targets the miR-218-5p/LMO7 Axis to Promote Chicken Embryonic Myoblast Proliferation and Differentiation - Shen, Xiaoxu; Wei, Yuanhang; Liu, Wei; You, Guishuang; Tang, Shuyue; Su, Zhenyu; Du, Mingxin; He, Jian; Zhao, Jing; Tian, Yongtong; Zhang, Yao; Ma, Menggen; et al. (Frontiers in Cell and Developmental Biology, 2021)
Circular RNA (circRNA) is a class of endogenous non-coding RNAs without 5′ and 3′ ends, rising studies showed circRNA is involved in skeletal muscle development. From our previous sequencing data, the circRNAome in breast muscle of two chicken lines with distinct rate of muscle development, which included a fast muscle growing broiler (FMGB) and a slow muscle growing layer (SMGL), we found a novel differentially expressed circRNA generated by intersectin 2 (ITSN2) gene (named circITSN2). We verified that circITSN2 is a skeletal muscle enriched circRNA which promotes chicken primary myoblasts (CPMs) proliferation and differentiation. Further molecular mechanism analysis of circITSN2 in chicken myogenesis were performed and we found circITSN2 directly targeting miR-218-5p. Besides, miR-218-5p inhibits CPMs proliferation and differentiation, which is contrary to circITSN2. Commonly, circRNAs act as a miRNA sponge to alleviate the inhibition of miRNAs on mRNAs. Thus, we also identified a downstream gene LMO7 was inhibited by miR-218-5p, while circITSN2 could block the inhibitory effect of miR-218-5p by targeting it. Functional analysis revealed that LMO7 also accelerates CPMs proliferation and differentiation, which was similar to circITSN2 whereas contrary to miR-218-5p. Taken together, these results suggested circITSN2 promotes chicken embryonic skeletal muscle development via relieve the inhibition of miR-218-5p on LMO7. Our findings revealed a novel circITSN2/miR-218-5p/LMO7 axis in chicken embryonic skeletal muscle development, which expand our understanding of the complex muscle development regulatory network.